Strategi Edukasi Wakaf Tunai untuk Buku Siroh Melalui Media Sosial untuk Mendorong Partisipasi Khalayak: - Efrita Norman; Hesty Hartiman; Enah Pahlawati; Arman Paramansyah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to find out the strategies used in the cash waqf movement for siroh books through social media in encouraging public participation in the Spirit Nabawiyah Community. The research method used to answer this research is descriptive qualitative research method. This method can be interpreted as one of the procedures in solving a problem under study by describing the subject or object in the research in the form of people, institutions, communities and others. The results of this study indicate that the strategy used is to expand the network (recruitment process) of community members who will become good connectors, then online class coaching activities are also held, as well as a continuous monitoring process that results in high public awareness to participate in the program. This is the month of Ramadan 1441 H. Keywords: Waqf Education, Social Media